Best Practices for Application Management - Bulusu, Lakshman (Oracle Embedded Programming and Application Development, 2011)
Code accelerators for rapid application development and management: Design and coding aspectsBest practices for application Web interaction: receiving, routing, responding, redirecting, rendering, linkingBest practices for application integrityBest practices for application consistencyBest practices for security beyond user authentication: End-to-end application securityBest fit for Oracle in the ASP.NET frameworkBest practices for templates: Use or eliminate?